Workshop Conclusions - 2nd Meeting of Informal Working Group on S&T - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The Advisory Committee on Science and Technology for ACP Agricultural and Rural Development was launched in December 2003. CTA hosted the 2nd Meeting of the ACP Informal Working Group (IWG) on Science and Technology, November 28 - December 03, 2003 in The